Manufacturing and photocrosslinking of a new bio‐based dimethacrylate resulting in hydrophobic crosslinked films. Issue 1 (17th December 2021) - Sanay, Berran; Strehmel, Bernd; Strehmel, Veronika
Abstract: A new bio‐based dimethacrylate (EMHO) consisting of three isomers, that is (ethane‐1, 2‐diyl‐bis(9‐methacryloyloxy‐10‐hydroxy octadecanoate) [EMHO‐i1], ethane‐1, 2‐diyl‐9‐hydroxy‐10‐methacryloyloxy‐9′‐methacryloyloxy‐10′‐hydroxy octadecanoate [EMHO‐i2], and ethane‐1, 2‐diyl‐bis(9‐hydroxy‐10‐methacryloyloxy octadecanoate [EMHO‐i3]), was made by a three‐step reaction starting from esterification of oleic acid with ethylene glycol followed by epoxidation in a second step, and epoxy ring‐opening reaction with methacrylic acid in a third step. The new dimethacrylate obtained was photocured applying ultra‐violet technology to receive a neat polymer on the one hand and in the presence of a further methacrylate, such as 4‐(4‐methacryloyloxyphenyl)‐butan‐2‐one (MAPO) or methyl 9‐(1H‐imidazol‐1‐yl)‐10‐(methacryloyloxy)‐octadecanoate and methyl 9‐(methacryloyloxy)‐10‐(1H‐imidazol‐1‐yl)‐octadecenoate available as isomer mixture (MIMAO), on the other hand. The photopolymerization kinetic study applying photo‐differential scanning calorimetry technology showed that the addition of MAPO or MIMAO during photocuring resulted in an increase in both polymerization rate and final conversion on monomer in comparison with the homopolymerization of EMHO. As expected, the network density obtained by the study of the elastic modulus of the copolymers was reduced compared to the homopolymer caused by the presence of the methacrylate MAPO or MIMAO comprising only one polymerizable functional group. The crosslinked polymer films contain high gel content. Those films made by using an excess of MAPO showed a glass transition above room temperature caused by the aromatic ring comprising in MAPO. High contact angle values for water indicate the high hydrophobicity of the crosslinked polymer films that is attributed to the long alkyl chains contained in the bio‐based dimethacrylate. The copolymer made from the bio‐based dimethacrylate with MAPO excess may be interesting for application as a water‐repellent coating for surface protection and protection against corrosion. Abstract : A new bio‐based dimethacrylate consisting of three isomers was synthesized, then photocured to receive a homopolymer or in the presence of bio‐based methacrylates comprising aromatic structures to yield copolymers. The polymer films contain high gel content, and the film made by using an excess of the methacrylate comprising a substituted phenyl ring showed a glass transition above room temperature. This copolymer may be interesting for application as a water‐repellent coating for surface protection and protection against corrosion, using more environmentally friendly raw materials for production processing.